Aktualisasi Sistem Green School dalam Meningkatkan Perilaku Hidup Bersih dan Sehat pada Siswa MI Gunungkidul Yogyakarta - Zarin, Puti Astias; Ichsan, Ahmad Shofiyuddin; Yunianta, Rohmat Dwi (EDUCASIA: Jurnal Pendidikan, Pengajaran, dan Pembelajaran, 2023)
This research aimed to analyze the actualization of the Green school system in improving clean and healthy living behavior in students at Madrasah Ibtidaiyah Negeri 4 Gunungkidul Yogyakarta. This research was a field research using descriptive qualitative method. Sources of research data obtained from interviews, observation and documentation. The method of data analysis used the concept of Miles and Huberman and tests the validity of the data using source triangulation techniques. The research results were that the habituation of caring for the environment and living clean and healthy had been made into a school program, such as integration in all subjects, using nature as a learning medium, maintaining the classroom environment, the student obligations to bring food and drinking bottles from home, clean the environment around the school every Friday, recycling garbage, and commemorating environmental days. It made the students realize that protecting the environment also means maintaining the cleanliness and health of themselves, others, and their environment. It made the students realize that protecting the environment also means maintaining the cleanliness and health of themselves, others, and their environment. From this habituation, students became accustomed to disposing of trash in its place according to the waste type, students were also used to picking up trash that was not in its place. In addition, students were also accustomed to washing their hands before and after activities. Factors supporting the implementation of the green school system included: strong motivation from teachers, village government and local government, supporting facilities and infrastructure, good cooperation, and conducive school locations and conditions. While the inhibiting factors were the lack of student discipline, lack of parental awareness, and the existence of the Covid-19 pandemic.